Trade tensions: Implications for Latin America and the Caribbean - Laborde Debucquet, David; Piñeiro, Valeria (International Food Policy Research Institute, 2019)
To better understand the likely impacts for Latin America and the Caribbean of developments in global trade, we modeled a set of four scenarios to see how escalating trade tensions would affect the region’s economies and the potential for a regional response to mitigate possible negative impacts. This article reviews the results of that modeling exercise.